Toolsets for the Development of Highly Interactive and Information-Rich Environments - Bowman, Doug A.; Hodges, Larry F. (International Journal of Virtual Reality, 1997)
This paper describes a unique set of programming toolsets which are designed specifically to aid in the authoring of immersive virtual environment (VE) applications. The first toolset provides a wide range of user interface options through a pen based metaphor, and benefits applications which have a high degree of interactive complexity. The second toolset allows high level control of audio annotations, and benefits applications which provide information to the user via the audio modality. The toolsets are designed to provide abstraction from the basic VE software system, to allow rapid prototyping and experimentation, and to be reusable across multiple applications. Two applications which have made extensive use of both toolsets are also presented.